HUBUNGAN ASUPAN ASAM FOLAT, VITAMIN B6, DAN VITAMIN B12 DENGAN NILAI ANKLE BRACHIAL INDEX PASIEN PENYAKIT ARTERI PERIFER PADA POPULASI DI KOTA MATARAM - Qurniadi, Margian Tri; Indrayana, Yanna; Irawati, Deasy (Faculty of Medicine Universitas Mataram, 2021)
Background: Peripheral Artery Disease (PAD) is partial to total blockage of blood vessels especially in the leg arteries. Ankle Brachial Index (ABI) can be used as a method of screening and diagnosis of PAD. Excess homocysteine is a risk factor of PAD. Deficiency of folic acid, vitamin B6, and vitamin B12 can disrupt homocysteine metabolism and increase the of PAD indirectly. Method: This study is a cross sectional study conducted at Siti Hajar Islamic Hospital in Mataram. The sample was patients with peripheral artery disease with an ABI value <0,90. The number of research samples was 52. The sampling technique used consecutive sampling method. Data analysis used the Spearman correlation test. Result: The average daily intake of folic acid, vitamin B6, and vitamin B12 in the study sample wass less than 50% of the recommended daily nutritional adequacy rate for Indonesians. The average ABI in the sample was 0,79. The results of the Spearman correlation test between ABI and folic acid intake showed a significance = 0,20 and coefficient correlation = 0,322. The results of the Spearman correlation test between the ABI and vitamin B6 intake showed a significance = 0,167. The results of the Spearman correlation test between ABI and vitamin B12 intake showed a significance = 0,800. Conclusion: There is a significant relationship between ABI and folic acid intake. There is an insignificant relationship between ABI and vitamin B6 and vitamin B12. Keywords: Peripheral Artery Disease, Ankle Brachial Index, Folic Acid, Vitamin B6, and Vitamin B12